2023
DOI: 10.3390/life13030600
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Systemic Inflammation Markers in Testicular and Penile Cancer: A Narrative Review of Current Literature

Abstract: In contemporary clinical practice, biomarkers are indispensable in the assessment and management of oncological patients. Although established serum tumor markers (beta human chorionic gonadotropin (bHCG), alpha fetoprotein (AFP), and lactate dehydrogenase (LDH)) have an indisputably important role in the management of patients with testicular cancer (TC), the application of these tumor markers may be accompanied with certain limitations, implying the need for additional biomarkers. Contrary to TC, there is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…(1) Alpha-fetoprotein (AFP): A protein produced during fetal development. Elevated AFP levels are commonly used as a diagnostic and monitoring tool for testicular cancer and can also predict the response to chemotherapy in patients [64]. (2) Human chorionic gonadotropin (HCG): HCG is a hormone produced during pregnancy, but elevated levels of HCG are also frequently observed in testicular cancer.…”
Section: Biomarkers In Testicular Cancers: Use In Early Detection Dia...mentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Alpha-fetoprotein (AFP): A protein produced during fetal development. Elevated AFP levels are commonly used as a diagnostic and monitoring tool for testicular cancer and can also predict the response to chemotherapy in patients [64]. (2) Human chorionic gonadotropin (HCG): HCG is a hormone produced during pregnancy, but elevated levels of HCG are also frequently observed in testicular cancer.…”
Section: Biomarkers In Testicular Cancers: Use In Early Detection Dia...mentioning
confidence: 99%
“…Studies have found that HCG levels can be a significant predictor of relapse in patients with testicular cancer [65,66]. (3) Lactate dehydrogenase (LDH): Elevated levels of LDH are associated with testicular cancer, and this metabolic enzime is often used as a predictor of overall survival in patients [64]. miRNAs: miRNAs are small RNA molecules involved in gene regulation; specific miRNAs are dysregulated in testicular cancer and can serve as biomarkers for the disease.…”
Section: Biomarkers In Testicular Cancers: Use In Early Detection Dia...mentioning
confidence: 99%
“…Similarly, lymphovascular invasion (LVI) has been recognized as a reliable prognostic factor for relapse in clinical stage I NSGCT patients, guiding risk-adapted treatment strategies [7]. Systemic inflammation indices, particularly the neutrophile-to-lymphocyte ratio (NLR), systemic immune-inflammation index (SII) and platelet-to-lymphocyte ratio (PLR), have demonstrated the potential for complementing and improving existing biomarkers and clinicopathological variables in GCT patients [8]. The utilization of advanced techniques like next-generation sequencing (NGS) and multiomics has led to the identification of several promising prognostic factors in TC patients [9,10].…”
Section: Introductionmentioning
confidence: 99%